EFFECTIVE METHODS OF USING COLLABORATIVE PEDAGOGY IN EDUCATION - BOBOEYEVA SABINAKHAN LAZIZ KIZI (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article discusses effective methods for using collaborative pedagogy in the educational process. The main principles of collaborative teaching, the importance of interaction between teacher and student, the role of working in small groups in the development of learning motivation and competencies are analyzed. The use of interactive methods in the lesson process, methods aimed at developing students' independent thinking, creativity and social skills are also considered. The results of the study show that the use of collaborative pedagogy increases educational effectiveness, increases student activity and improves the level of mastery